Major Public Health Issue as a Vehicle for Interprofessional Curriculum: A Simulated Obesity Module Involving Seven Disciplines - Gerald Wickham; Joel Gordon; Michael Kelly; Paula Weistroffer; Jill Valde; Janet Hosking; Laura Law (Association of American Medical Colleges, 2013)
Abstract Introduction This resource seeks to continue the longitudinal development of a modular and portable curriculum in interprofessional health sciences education. This is a curriculum that prepares health sciences students for teamwork in treating patients with the leading public health problem in America: obesity. Methods This curriculum involves a patient case, simulated patient training, and faculty development for the case activity and associated learning resources. This module offers the opportunity to learn from other health care professionals, about health sciences disciplines, while providing teamwork and communication experience with peer health science learners. This module is portable and adaptable to most academic health centers; we have run this curriculum with up to 375 learners, utilizing 75 faculty members from all of the disciplines over a 4-day timeframe. Results The effectiveness of this curriculum in strengthened by the heterogeneous nature of it. The combination of large group plenary sessions, small group discussion groups, and team-based and patient panels offers a variety of opportunities to learn about obesity in several different ways. Longitudinal tracking of student perceptions of the interdisciplinary cases demonstrates improvement over time, with a 2001 mean of 3.36 on a scale of 1 through 5. Discussion This represents ground-breaking curriculum in interprofessional education at the University of Iowa. It demonstrates to deans and other administrators that interprofessional education at the University of Iowa Health Sciences campus can work, does work, and should be expanded as new curricula in all of the health sciences is developed.